EVALUASI PENERAPAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI SEKOLAH DASAR - Padmono, Yohanes (Jurnal Inovasi Pendidikan, 2010)
The objectives of this study are to evaluate the implementation of KTSP curriculum at Elementary school in Kebumen, Central Java province. The significance of the implementation of curriculum is (1) usefulness, (2) Normative Appropriateness, and (3) the accuracy of implementation. The indicators of significance can be elaborated as follows: (1) the synergy of collegial model to construct KTSP curriculum, (2) KTSP curriculum prototype for elementary school, (3) teacher's syllabus prototype, (4) the implementation mechanism to construct, (5) the appropriateness of KTSP curriculum prototype for the school. (6) The appropriateness of syllabus for class, (7) the usefulness of KTSP for school development. The subjects of this study were 13 from 56 elementary schools throughout Kebumen sub districts of Kebumen district, Central Java Province. Checklist, Questionnaires, interview, and observation were used to collect the data. The findings show that: (1) the synergy of collegial model to construct KTSP is at the enough score, namely 62,5%, but the synergy is only ceremonial activity, (2)There are 66,6% of prototypes of KTSP curriculum are constructed in the elementary schools, but they are, (3) the teachers construct 100% of the syllabus but the prototypes are similar to the sample given or only in a copy-paste way, (4) 65,5% of the elementary schools imple-ment the mechanism, (5) 83,3% of KTSP curriculum prototypes are appropriate for the schools, (6) the appropriateness of the syllabus for classes is 100%, (7) 53,5% of KTSP curriculum is useful for the school development. The findings show that the imple-mentation of KTSP curriculum is recommended along with the use of prototype of KTSP curriculum in the synergy of collegial model. However, in practice, there should be some improvement to encourage the teacher's competence to construct KTSP curriculum itself.